2017
DOI: 10.1038/srep45315
|View full text |Cite
|
Sign up to set email alerts
|

Specialist nectar-yeasts decline with urbanization in Berlin

Abstract: Nectar yeasts are common inhabitants of insect-pollinated flowers but factors determining their distribution are not well understood. We studied the influence of host identity, environmental factors related to pollution/urbanization, and the distance to a target beehive on local distribution of nectar yeasts within Robinia pseudoacacia L. and Tilia tomentosa Moench in Berlin, Germany. Nectar samples of six individuals per species were collected at seven sites in a 2 km radius from each target beehive and plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Belisle et al ., ; Vannette & Fukami, ), while A. pullulans has a broader habitat range (e.g. Andrews et al ., ; Wehner et al ., ). The ecological affinities of the bacterial taxa profiled here are unknown, but strains from these genera have been found in floral nectar in other studies previously (Vannette et al ., ; Good et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Belisle et al ., ; Vannette & Fukami, ), while A. pullulans has a broader habitat range (e.g. Andrews et al ., ; Wehner et al ., ). The ecological affinities of the bacterial taxa profiled here are unknown, but strains from these genera have been found in floral nectar in other studies previously (Vannette et al ., ; Good et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Many of these species are found almost exclusively in nectar or on the animals that visit flowers to forage for nectar such as bees and hummingbirds (Belisle, Mendenhall, Brenes, & Fukami, ; Brysch‐Herzberg, ). Nectar microbes rely on these animals for dispersal among flowers (Belisle et al., ; de Vega, Herrera, & Johnson, ; Wehner, Mittelbach, Rillig, & Verbruggen, ). As such, flowers represent discrete and ephemeral habitats (Toju, Vannette, Gauthier, Dhami, & Fukami, ) where environmental sorting and dispersal limitation can be studied relatively easily (Belisle, Peay, & Fukami, ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the microorganisms that exhibited increases or decreases in relative abundance between the three sites were those most commonly found in other nectar microbiome studies [34,[74][75][76][77][78][79]. Acinetobacter has been identified as a nectar specialist efficient at producing acid from the metabolism of both glucose and sucrose [80], two sugars commonly found in A. curassavica nectar [47].…”
Section: Discussionmentioning
confidence: 95%